Cancer Treatment: An Epigenetic View - Aydin, Cansu; Kalkan, Rasime (Global Medical Genetics, 2020)
Cancer can be identified as an uncontrolled growth and reproduction of cell. Accumulation of genetic aberrations (mutations of oncogenes and tumor-suppressor genes and epigenetic modifications) is one of the characteristics of cancer cell. Increasing number of studies highlighted importance of the epigenetic alterations in cancer treatment and prognosis. Now, cancer epigenetics have a huge importance for developing novel biomarkers and therapeutic target for cancer. In this review, we will provide a summary of the major epigenetic changes involved in cancer and preclinical results of epigenetic therapeutics.
Keywords: cancer; treatment; epigenetics; epidrugs; methylation